An assessment of the ozone loss during the 1999-2000 SOLVE/THESEO 2000 Arctic campaign - Schoeberl, M. R.; Newman, P. A.; Lait, L. R.; McGee, T.; Burris, J.; Browell, E. V.; Grant, W.; Richard, E.; Bevilacqua, R.; Mikkelsen, I. S.; von der Gathen, Peter (Journal of Geophysical Research, 2002)
Ozone observations from ozonesondes, the lidars aboard the DC-8, in situ ozonemeasurements from the ER-2, and satellite ozone measurements from Polar Ozone and AerosolMeasurement III (POAM) were used to assess ozone loss during the Sage III Ozone Loss andValidation Experiment (SOLVE) and Third European Stratospheric Experiment on Ozone(THESEO) 1999-2000 Arctic campaign. Two methods of analysis were used. In the first method asimple regression analysis of the data time series is performed on the ozonesonde and POAMmeasurements within the vortex. In the second method the ozone measurements from all availableozone data were injected into a free-running diabatic trajectory model and were carried forward intime from 1 December to 15 March. Vortex ozone loss was then estimated by comparing the ozonevalues of those parcels initiated early in the campaign with those parcels injected later in thecampaign. Despite the variety of observational techniques used during SOLVE, the measurementsprovide a fairly consistent picture. Over the whole vortex the largest ozone loss occurs between550 and 400 K potential temperatures (~23-16 km) with over 1.5 ppmv (~55%) lost by 15 March,the end of the SOLVE mission period. An ozone loss rate of 0.04-0.05 ppmv/day was computed for15 March. The total column loss was between 44 and 57 DU or 11-15%. Ozonesondes launchedafter 15 March suggest that an additional 0.5 ppmv or more ozone was lost between 15 March and1 April.